Cyclic efforts to improve completion rates of masters' degree students in nursing - Lizeth Roets; Yvonne Botma (AOSIS, 2012)
Supervisors at Higher Education Institutions are challenged to shorten throughput of Master's degree students in nursing as researchers are needed to improve the art and science of the nursing profession. Globally the completion time for a postgraduate degree in the health sciences varies between 4.7 and 5.5 years. The purpose of the study was to describe strategies that were implemented to shorten completion time and attrition rate of postgraduate students. A cyclic technical, scientific collaborative mode within an action research methodology was used to identify factors impeding completion time in this study. Contrary to other studies, supervision was not an inhibiting factor in this study. Physical, technical, academic and financial aspects were identified by postgraduate students through questionnaires and informal discussion groups with supervisors as well as progress reports. Strategies were implemented to address these. Following implementation of all strategies, 42% of the postgraduate students in the School of Nursing completed their Master's degree within two years. This implies a 34% improvement. Although the completion rate improved it was still unsatisfactory and new challenges were identified during the second cycle, for example, the number of inexperienced supervisors increased and they needed mentoring. Speed mentoring is a possible solution to the problem.